PEMIKIRAN HERMEN¬EUTIKA WILHELM DILTHEY (1833 – 1911 M) - Sholikah Sholikah (Al Hikmah: Jurnal Studi Keislaman, 2017)
In life, everyone will always be faced with the situation to understand everything that exists and is found in his life, whether it is text or context. Therefore a variety of theories and methods were born to understand them. Hermenutics is one of the many theories and methods to uncover meaning, so it can be said that hermeneutics has the main responsibility in uncovering and displaying the meaning behind the symbols that become the object. Wilhelm Dilthey is a philosopher who is famous for his philosophy of life, which states that life is a series of human experiences that became the history of his life which is widely and comprehensively understood. In his hermeneutic project, Dilthey provides a new definition of experience (erlebnis), meaning (ausdruck) and understanding (verstehen). He himself relies on art as a hermeneutic object. With the historical method, Dilthey tries to provide a new understanding in interpreting a series of human experiences whether it be in the form of text, biography and so on. Dilthey is a philosopher who was very inspired by the previous philosopher, Schleirmacher. But Dilthey added history in his epistemology. Dilthey considers that text is a symbol, not a word meaning. So to understand a symbol, the interpreter must go to history, in other words must be part of history itself. Wilhem Dilthey's thought in his hermeneutics was to formulate a unique methodology in Geisteswissenschaften (human science) considering he believed that the Naturensensaftan (nature science) method was not appropriate for human science. Sometimes Geistenwissenscaften also uses Naturwissenschaften objects, but the context of the relationship is different. Dilthey sees that verstehen (understanding) is a method for human science where it is clearly a method for nature science. With human expression using a purely intellectual process. Whereas with verstehen, humans use cooperation in all their mind abilities in the activity of understanding and understanding.